TRAINING ON MAKING A WATER LEVEL INSTRUMENT AS AN EARLY WARNING SYSTEM FOR PEATLAND IN TUMBANG TAHAI VILLAGE, CENTRAL KALIMANTAN - Cassiophea, Lola; Ni Putu Diah Agustin Permanasuri; Indah Gumilang Dwinanda; Mega Kurniawati (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2023)
Indonesia has 14,905,575 ha of peatlands spread across Sumatra (43.18%), Kalimantan (32.06%) and Papua (24.76%) (Balai Besar Sumberdaya Lahan Pertanian, 2011). The area of peatland in Central Kalimantan reaches 2.65 million ha or 16.83% of the total area of Central Kalimantan (Balai Besar Litbang Sumberdaya Lahan Pertanian, 2013). Land and forest fires are becoming increasingly severe not only in Central Kalimantan, but also in other regions. This is triggered by activities where peatlands are used for agriculture or plantations coupled with the construction of drainage canals, causing peat water to dry out and become flammable during the dry season. In 1997, catastrophic fires destroyed no less than 2.2 million hectares of peat swamp forest, and destroyed 0.14 - 0.17 Gt of peatland carbon. In addition, it also caused several health problems, for example in Central Kalimantan, during the fires in 2015 there was data on cases of acute respiratory infections (ARI) in Central Kalimantan until the fourth week of September 2015, the number of sufferers reached 20,274 people (KMNLHRI and UNDP; 2015). These forest fires also cause great losses in the socio-economic field. This service aims to prevent drought in peatlands by measuring the water level at several points in Tumbang Tahai Village by measuring the water level so that an Early Warning System for peatland drought is formed in the village. It is hoped that the community of Tumbang Tahai Village in particular and the people of Central Kalimantan in general will be able to prevent peatland drought and this can be an initial experience in the practical experience of making, installing and using a water level measuring instrument.